A probabilistic model of pedestrian crossing behavior at signalized intersections for connected vehicles. (October 2016) - Hashimoto, Yoriyoshi; Gu, Yanlei; Hsu, Li-Ta; Iryo-Asano, Miho; Kamijo, Shunsuke
Highlights: We present a probabilistic model of pedestrian behavior at signalized intersections. The proposed model is constructed using the Dynamic Bayesian Network. Context information and pedestrian behavior are integrated in the model. The model recognizes pedestrian crossing intention with high accuracy in short time. Abstract: Active safety systems which assess highly dynamic traffic situations including pedestrians are required with growing demands in autonomous driving and Connected Vehicles. In this paper, we focus on one of the most hazardous traffic situations: the possible collision between a pedestrian and a turning vehicle at signalized intersections. This paper presents a probabilistic model of pedestrian behavior to signalized crosswalks. In order to model the behavior of pedestrian, we take not only pedestrian physical states but also contextual information into account. We propose a model based on the Dynamic Bayesian Network which integrates relationships among the intersection context information and the pedestrian behavior in the same way as a human. The particle filter is used to estimate the pedestrian states, including position, crossing decision and motion type. Experimental evaluation using real traffic data shows that this model is able to recognize the pedestrian crossing decision in a few seconds from the traffic signal and pedestrian position information. This information is assumed to be obtained with the development of Connected Vehicle.